Chromosomal Control of Mating Activity in Drosophila pseudoobscura - Sherwin, Richard N. (National Academy of Sciences, 1973)
Lines containing two third-chromosome inversions (Arrowhead and Pikes Peak) of Drosophila pseudoobscura selected for fast and slow mating speed were crossed to a multichromosomal, dominant marker inversion stock, and strains with various combinations of chromosomal derivation were tested for their mating activity. When lines were selected isodirectionally with the known third-chromosome control, the third chromosome was found to possess major epistatic control over mating speed, followed by the fourth, with no appreciable effect from the first and second. However, polygenic modification mating activity was found throughout the genome when selection was applied opposite to the original third-chromosome control. The work reported here strengthens the evidence that the adaptive role of chromosomal polymorphism has a behavioral basis in mating activity.